Common words Kazakh-Persian languages – the result against the historical, cultural, political and economic - Naralieva R Т; Masimbaeva А А (Journal of Oriental Studies, 2016)
The authors consider loan words in Kazakh and Persian languages as a result of cultural, economic and political relations between these countries.